What if Dru Johnson Is Right?: Possible Implications of Hebraic Philosophy for Systematic Theology and the Doctrine of God - Mullins, R. T.; Johnson, Dru 1974- (2024)
What if Dru Johnson is correct that the Bible is philosophy? I consider the implications of this for systematic theology and the doctrine of God. I argue that classical theism, Reformed Thomism, and other such positions are rival philosophical schools of thought that contradict the Bible’s philosophical reflections on God.
Keywords: Rezension